Regenerasi Pengrajin Gerabah Perempuan di Pundong, Kasongan, dan Bayat dalam Mempertahankan NilaiNilai Kearifan Lokal Budaya Jawa - Suharson, Arif (PANGGUNG, 2024)
This research discusses women traditional pottery craftsmen in Pundong, Kasongan, and Bayat who are guardians of local cultural traditions in the midst of a global cultural ecosystem that is changing rapidly. This study aims to analyze the role of women in maintaining the values of local wisdom and how they deal with the influence of globalization on their traditional pottery crafts in relation to regeneration. The method used is a qualitative method with an ethnographic approach model. Data collected included observations, interviews, and documentation in traditional pottery-making communities. Pottery craftsmen in Pundong, Kasongan, and Bayat play an important role as custodians of cultural knowledge, transmission of traditions, and innovation in pottery crafts. The expertise of traditional techniques, artistic expression, and cultural symbols is a testament to women's dedication in maintaining the values of local wisdom amid the pressures of the global cultural ecosystem. The results of this study contribute to a broader understanding of the importance of cultural preservation and regeneration efforts involving gender roles in learning the nation's character. Keywords: Women, Pottery Craftsman, Local Wisdom, Global